Relationship Between The Covid-19 Pandemic And The Decreasing Number Of Tourists In The Tourism Sector: Systematic Literature Review - Cantikya Rahma Hadi; Setiawan; Ainindya Putri Pujiyanto; Laras Dina Revindha; Nisa Cahya Soleha (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
The COVID-19 pandemic, which has been going on for a long time in several countries, is one of the reasons for the decline in tourists in several tourism industries in the world, including Indonesia. The COVID-19 pandemic situation has caused a breakdown in global supply chains, domestic, financial markets, consumer demand. The impact of the Covid-19 pandemic was enormous and affected the entire Tourism/UKM value chain which is also the creative economy sector. The purpose of this research was to determine the decline in the number of tourists in Jojogan nature tourism during the COVID-19 pandemic. This research method describes the procedures and steps for conducting a review which include: Review method; scoping review is a method used to identify in-depth and comprehensive literature obtained through various sources with various research methods and related to the research topic. The results of the number of articles selected based on databases, namely Pubmed, Ebsco Host, and Scopus, found that there were 6 articles that had been selected. COVID-19 is one of the reasons for the decline in the number of tourists in the tourism industry. The decline in the number of tourists greatly affected several industrial sectors, especially the food industry, the health industry and the financial industry. The suggestion is that several ways to increase the number of tourists and reduce the spread of COVID-19 have been carried out, namely by creating new trends and appearances at these tourism spots, then to reduce the number of spreads of COVID-19 conducting health checks for all tourists who will visit.